2020
DOI: 10.36227/techrxiv.11672532.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of Systematic Bias in Measuring Surface Deformation with SAR Interferometry

Abstract: <div>This paper investigates the presence of a new interferometric signal in multilooked Synthetic Aperture Radar (SAR) interferograms which cannot be attributed to atmospheric or earth surface topography changes. The observed signal is short-lived and decays with temporal baseline; however, it is distinct from the stochastic noise usually attributed to temporal decorrelation. The presence of such fading signal introduces a systematic phase component, particularly in short temporal baseline interferogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…The main drawback is that the result can be biased because the unwrapping error is introduced (i.e., by adding a wrong integer ambiguity number 2π during the phase unwrapping). Furthermore, it may be not suitable for studying at local-scale deformations [25,27] and it also has a non-closure phase biased due to working on multilook imagery [28][29][30]. In contrary, in the second approach, the analysis can be carried out using the wrapped phase in model Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The main drawback is that the result can be biased because the unwrapping error is introduced (i.e., by adding a wrong integer ambiguity number 2π during the phase unwrapping). Furthermore, it may be not suitable for studying at local-scale deformations [25,27] and it also has a non-closure phase biased due to working on multilook imagery [28][29][30]. In contrary, in the second approach, the analysis can be carried out using the wrapped phase in model Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding maps are computed for 6, 12, or 18-day interferograms. They quantify the bias associated with seasonal vegetation growth, which is introduced by interferogram multi-looking nonlinearity, and which fades with interferogram duration (Ansari et al, 2020). Pixels with large positive or negative bias on the 18-day MLDI map were masked (Figure S1b in Supporting Information S1).…”
Section: Sentinel-1 Data Processingmentioning
confidence: 99%
“…While the interferometric phase values approach normality as the resolution is degraded, at the 30 m spatial resolution selected for the data products generated from the PDO joint retrieval, interferometric phase still exhibits a degree of kurtosis, which can complicate ALT estimates when only a single interferogram is available. A recent study demonstrated that the choice of temporal baseline in InSAR time series analysis can similarly introduce interferometric phase biases (Ansari et al, 2020). Much like this counterintuitive result, the choice of spatial resolution may similarly introduce phase biases into both individual interferograms and time series analyses, necessitating further research into interferometric phase biases which are not directly related to geophysical deformation.…”
Section: Effect Of Spatial Resolution On Measured Phasementioning
confidence: 99%